Profile of analgesic prescription by medical specialties: A comparative study of symptomatic management in emergency care between orthopedics and other specialties–A retrospective observational brief report - Luis Fernando Penna; Adhan A. Wu; Ricardo Madureira; Ricardo Luiz A. Fonseca; Renata Kobayasi Zelada; Fernando Ganem; Christian V. Morinaga (PLoS ONE, 2025)
Study objective This study aims to analyze whether specific medical specialties are associated with potentially inappropriate analgesic prescriptions by examining and identifying variables related to both patient and prescriber profiles that influence certain analgesic choices. Methods This is a retrospective longitudinal observational cohort study conducted based on medical records and charts from the Emergency Department (ED) at Hospital Sírio-Libanês (HSL), Bela Vista Unit, São Paulo, Brazil, from 2019 to 2022. It includes patients treated for pain with symptomatic medication administered alone or in combination, with outcomes assessing the efficiency of associations and the need for additional drugs. Results Among 154,404 adult ED visits, 16,787 patients met the inclusion criteria. Orthopedics had a higher proportion of male patients (45.0%) with an older average age of 48.1 (±14.7) years. Additionally, 60.6% of these cases were classified as having a relatively urgent risk, and only 2.1% were emergencies. Orthopedic specialists had a higher likelihood of prescribing Level 2 and Level 3 analgesics, as well as being more likely to require rescue medication. Conclusion The “Orthopedics” specialty prescribed more potent and a higher number of initial analgesics compared to other specialties, with a greater proportion of patients receiving rescue medications.